REPRODUCTIVE PERFORMANCE OF RED SOKOTO GOAT BREED IN ADAMAWA STATE (FUDMA JOURNAL OF SCIENCES, 2023)
As a multipurpose animal, goats provide meat, milk, hides, skin, and manure. They rank next to cattle in income generation and their meat (chevon) is quite popular and well-relished. The need to develop productive and adaptive goat breeds. This study was carried out to investigate the reproductive performance of Red Sokoto goat in Adamawa state. The design of the experiment was based on supplements offered. The result obtained in the study was; gestation length was short in groups receiving maize bran and cotton seed cake but longer in the control group and significant differences (P
Keywords: Birth weight; gestation length; Red Sokoto goat; supplementation; twinning rate